A report on the physicochemical and antioxidant properties of three Indonesian forest honeys produced by Apis dorsata - Mahani; Pamungkas Rizki Ferdian; Habil Muhammad Ghibran; Amirah Fathia Herlina; Siti Nurhasanah; Nunung Nurjanah; Rizki Rabeca Elfirta; Avry Pribadi; Raden Lia Rahadian Amalia; I Made Samudra (Food Chemistry: X, 2025)
Indonesia, one of the largest tropical forests, offers a diverse range of nectar sources that contribute to the unique characteristics of forest honey. This study aims to investigate physicochemical and antioxidant properties of Apis dorsata forest honey from three distinct regions of Indonesia. Key physicochemical parameters include moisture, color, electrical conductivity (EC), total dissolved solids (TDS), total suspended solids (TSS), density, diastase number (DN), hydroxymethylfurfural (HMF), pH, total acidity, ash content, protein content, and reducing sugars. Antioxidant properties, assessed through total phenolic content (TPC), total flavonoid content (TFC), DPPH radical scavenging activity, ascorbic acid equivalent antioxidant capacity (AEAC), and ferric reducing power (FRP), revealed significant regional variability. Principal component analysis (PCA) distinguished honey samples based on these attributes. These findings provide preliminary insights into the variability of Indonesian forest honeys. However, the small sample size limits generalizations, and further research with larger datasets is essential for validation.